(3Gddjd aj GdbQBf GdcQje (B:s (3OQGSI LeGdjI (B/s - (3SYjO, SYO LQLjS,s 1979- ((3OeTb, ShQjI ;s (3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3UaMGJ ddOQGSGJ hGdfTQ hGdJhRjY,s, 2016)
(3Gddjd YfO GdLGgdjjf cGf eTMhfG HGdbdb hGdNha hGdhMTI hGdGVWQGH, cGf aj eNjdI GdLGgdj Cf Gddjd YGde jehL HGdLf hGdCTHGM, CeG djd GdbQBf GdcQje agh BfGA QNjI ddYHGOI hefGLGI Gddg, hGdJacQ aj bOQJg GdHGgQI hYdeg GdhGSY(B. (3Ef GdbQBf GdcQje bO hVY ddeDefjf LejY GdSHd GdJj Jecfge ef GdJYGed eY Gddjd, hCYWGge GdeaGJjM GdJj HgG jONdhf Edjg, abO CQTOge GdbQBf Edi BjGJ Gddjd, haj GdhbJ faSg Ydege cja jfXQhf EdjgG hjJOHQhfgG, ceG Ydege cja jLYdhf ef Gddjd BfGA CfS hehOI hNThY(B. (3de jcJa GdbQBf GdcQje HJUhjQ Gddjd ef LgI hGMOI, hde jJMOK Yfg Ydi hab Ref eYjf, hEfeG GTJed Ydi JUhjQ Gddjd GdcHjQ ef LejY LgGJg haj LejY ChbGJg, ade JZH LgI hdG dMXI ef Gddjd Yf GdJUhjQ GdbQBfj, adSfG fHGdZ EPG bdfG (B: (3Ef GdNWaI GdSQjYI ddTgGH GdeJbO, hGdheVI GdNGaJI ef GdfLhe GdHYjOI, cGfJG MGVQJjf aj JUhjQ GdbQBf GdcQje(B.s
Keywords: (3GdbQBfs -- (3HdGZIs